2014
DOI: 10.2215/cjn.02840314
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Catalytic Iron, AKI, and Death among Critically Ill Patients

Abstract: Background and objectives Catalytic iron has been hypothesized to be a key mediator of AKI. However, the association between plasma catalytic iron levels and AKI has not been well studied in humans.Design, settings, participants, & measurements A single-center, prospective, nonconsecutive cohort study of 121 critically ill patients admitted to intensive care units (ICUs) between 2008 and 2012 was performed. Plasma catalytic iron, free hemoglobin, and other iron markers were measured on ICU days 1 and 4. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…Since that time, additional studies have added to the growing body of literature suggesting that anemia and the use of packed red blood cells are independent risk factors for AKI after cardiac surgery (145)(146)(147). Catalytic iron (i.e., circulating iron not bound to any proteins) can produce hydroxyl radicals, cause oxidative tissue damage, and has been proposed as a nephrotoxin (148). A recent analysis of catalytic iron levels in a population of patients who were critically ill found a strong relationship between the amount of blood products transfused and catalytic iron levels as well as between catalytic iron levels and the probability of developing AKI, suggesting a potential mechanism for the relationship between blood product transfusion and AKI (148).…”
Section: Perioperative Transfusion Of Packed Red Blood Cellsmentioning
confidence: 99%
“…Since that time, additional studies have added to the growing body of literature suggesting that anemia and the use of packed red blood cells are independent risk factors for AKI after cardiac surgery (145)(146)(147). Catalytic iron (i.e., circulating iron not bound to any proteins) can produce hydroxyl radicals, cause oxidative tissue damage, and has been proposed as a nephrotoxin (148). A recent analysis of catalytic iron levels in a population of patients who were critically ill found a strong relationship between the amount of blood products transfused and catalytic iron levels as well as between catalytic iron levels and the probability of developing AKI, suggesting a potential mechanism for the relationship between blood product transfusion and AKI (148).…”
Section: Perioperative Transfusion Of Packed Red Blood Cellsmentioning
confidence: 99%
“…136, 137 Based on experimental and human studies, iron is increasingly recognized to be a major culprit in AKI. 138140 To study iron trafficking and its role in AKI, we recently generated a novel transgenic mouse model with conditional deletion of heavy chain ferritin (FtH) in renal proximal tubules. 100 Interestingly, these mice exhibit significantly higher levels of HO-1 expression both under basal and injury conditions.…”
Section: Recent Advancesmentioning
confidence: 99%
“…Bobbio‐Pallavicini et al () investigated 51 postoperative critically ill patients and found that the increase in ferritin concentration correlated with worsening of the clinical status. In a prospective observational cohort study of 121 critically ill patients, plasma catalytic iron levels on ICU day 1 were significantly associated with hospital mortality and 30‐day mortality (Leaf et al, ). These results could be explained by the common inflammation, especially infectious inflammation, in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%